Management of Productive Zakat Management of Mustahic Welfare in Baznas Gorontalo District - Annisa Rizqa Alamri; Jenal Igrisa; Desca Thea Purnama; Mutmainnah Mutmainnah; Marini Marini; Reiki Nauli Harahap; Nurul Adha (Prosperity: Journal of Society and Empowerment, 2023)
Study this intended to analyze and describe productive zakat management to the well-being of Mustahik at Baznaz Gorontalo Regency. Problem-related to well-being Mustahik is interesting for research because Welfare is a condition that is the hope of every citizen. However, not all citizens quickly get Welfare, especially Mustahik. This study used a qualitative approach with descriptive analysis and data collection techniques using observation, interviews, and documentation. The results from the survey are organizing zakat BAZNAS Gorontalo Regency, namely by forming sub-sectors to support operational running management zakat, namely the zakat collection unit (UPZ), which is responsible for collecting zakat from muzak and implementing it as in the distribution and utilization of productive zakat in management, namely the distribution is uneven because the people in Gorontalo Regency have different economic conditions. Novelty in this research is that we found Supervision in the direction of zakat is carried out by forming an internal audit unit to oversee the work system implemented by each implementing area.